Weverse: partisipasi penggemar dalam komunitas mobile - Pravianti, Shavira Arisa (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study aims to illustrate how fan communities on Weverse application manifest a form of mobile community. Employing a qualitative approach with netnography methods, this research gathered data through observation and semi-structured interviews to analyze interactions and dynamics within the community. Data was collected through observation and semi-structured interviews. The findings reveal that the spatial, temporal, and contextual flexibility afforded by the mobile application allows fans to remain connected and actively participate, even under conditions of high mobility. These interactions, including communication, collaborative community activities, and content distribution, demonstrate how Weverse has become a digital space integrated into users' daily lives.